Caracterização genética e de virulência de Nc-UDI4, isolado de Neospora caninum, obtido em galinha - Silva, Mariana Ferreira (2021)
Neospora caninum is a protozoan that belongs to the Apicomplexan phylum, has worldwide distribution and causes neosporosis. This disease induces abortions in cattle and has a significant economic impact. There are no treatment nor vaccines against the parasite so, it is important to study the parasite and its relationship with the environment. It is known that birds are reservoirs for N. caninum, but the actual relevance of neosporosis in birds it is not clear yet. In the present work we aimed to characterize the genotype of a new strain of N. caninum isolated from the brain of a chicken in the city of Uberlandia/MG, Brazil, and compare its biological features with Nc-1 and Nc-Liv. Serological analysis showed that this new strain induces anti-N. caninum antibodies in mice and, using polymerase chain-reaction (PCR), we amplified the Nc5 sequence in its genomic DNA. Furthermore, Nc-UD4 genome aligned 99,8% to the reference genome, Nc-Liv, according to new generation sequencing (NGS) analysis. We identify single nucleotide polymorphisms (SNPs) and insertions/deletions (InDels) between Nc-UDI4 and Nc-Liv. Genes related to adhesion, invasion and survival of the parasite were altered and, as we showed in plaque assay, Nc-UDI4 had lower invasion/replication rates compared to Nc-Liv. Microsatellite analysis shared N. caninum in two clusters and revealed that the genotype of Nc-UDI4 is closely related to the Argentinian strains and Nc-1. Nc-UDI4 and Nc-1 are less virulent than Nc-Liv, as it induced low mortality of C57BL/6 mice and also a different cytokine profile. In that sense, mice infected with Nc-UDI4 and Nc-1 are more resistant to the infection, allied to a more favourable balance of pro- and anti-inflammatory immune responses against N. caninum, while Nc-Liv modulated this response in its favor, contributing to a worst outcome to its host.